Characteristics of malignant neoplasias at gastrointestinal tract. Callao 1991-1995 - Bermúdez, Alejandro (1996)
Objetive: To find out the distribution and some characteristics of malignant neoplasias of the gastrointestinal (GI) tract in a population of Callao - Peru. Design: A descriptive, retrospective and observational study. Context: GI unit, Daniel Carrion Hospital, Callao, Peru. Participants: Each patient with an histologically documented GI tract cancer, between November 1991 and March 1995, was included in the study. Pancreatic carcinomas were also considered with a positive CAT scan and/or ERCP study. Intervention: Clinical records, were included, 63.1% were males. The most common location was in stomach (57.3%), colon and rectum (15.5%) and hepatic carcinomas (9.9%). Gastric carcinoma was found in persons aged 45 or younger in 12% cases. Only 22% of gastric cancers were located on the antrum, 80% of colorectal cancers were located on the left hemi-colon rectum. Ampullocarcinoma was 1.8 times more frequent than pancreatic cancer. Conclusions: GI tract cancer was more frequent in the male population. The most common location is stomach, 12% of the total were found in young patients, 80% of colon carcinomas are approachable by the sigmoidoscopé. Ampullocarcinoma is more frequent than pancreatic cancer.